Factors Affecting of Use of LMS in Indonesia - Prakarsa, Graha; Sudirman, Iman; Affandi, Azhar; Santoso, Ferry (Universitas Insan Cendekia Mandiri, 2024)
The rapid growth of e-marketplaces in Indonesia today, has led to many users adopting the system, due to the large number of e-marketplace mobile applications, making it necessary for developers to know and pay attention to several factors that influence users in adopting e-marketplace application systems at this time, one of which is the only cost factor is perceived by the user. Data were collected as many as 100 respondents who had some experience in using e-marketplaces on a mobile basis, then analyzed using partial least squares-structural equation modeling (PLS-SEM). This research is based on the conceptual framework of the Unified Theory of Acceptance and Use Technology (UTAUT). The constructs used in this study are performance expectancy, effort expectancy, social influence, and facilitating conditions, but also add a perceived cost variable. The results show that performance expectancy, effort expectancy, and perceived cost have a positive and significant effect on the actual use of mobile e-marketplace users in Indonesia, but social influence and facilitating conditions do not significantly affect the actual use of mobile e-marketplace applications in Indonesia.